2D MPS analysis of hydrodynamic fine fragmentation of melt drop with initial steam film during fuel–coolant interaction. (July 2020) - Li, Gen; Wen, Panpan; Feng, Haobo; Zhang, Jun; Yan, Junjie
Highlights: Breakup behavior of melt drop with initial steam film was modeled using MPS method. Numerical models were validated with K-H and R-T instabilities and liquid drop breakup. Steam film rapidly moved away, which had insignificant effect on melt drop breakup. Melt fragment amount, size distribution and contact perimeter were analyzed. Abstract: The hydrodynamic fine fragmentation of melt drops, which increases the melt–coolant contact area and affects heat transfer and melt oxidation, is an important phenomenon during fuel–coolant interaction. The presence of a steam film surrounding the melt drops complicates the breakup simulation, including interface instabilities and high-density ratio. In this study, we modeled the breakup behavior of a melt drop with an initial steam film by using the meshless moving particle semi-implicit (MPS) method in the Lagrangian frame. Numerical models were validated step by step by simulating Kelvin–Helmholtz instability, Rayleigh–Taylor instability, and liquid drop breakup. The breakup behavior of a UO2 melt drop with and without initial steam film was simulated in 2D, and the fragment number, size distribution, and melt–coolant contact perimeter were comparatively analyzed. Results indicate that the initial steam film rapidly moved away from the melt drop and separated into two main bubbles, which had insignificant influence on either the melt drop deformation or the fragment number and the perimeter. The total number of fragments increased at the initial moments of the breakup process due to the flow inertia force and then decreased under the effect of surface tension. The number of small fragments ( d/d 0 = 0.01–0.03) increased and decreased in variations, but other relatively large fragments continuously increased in the entire duration. The perimeter contribution of small fragments was larger than those of other fragment groups in the initial duration of the melt drop breakup at We = 655, but it reversed subsequently. By contrast, the perimeter contribution by fragments with d/d 0 = 0.01–0.02 and 0.02–0.03 was constantly larger than those of other groups at We = 2618. Moreover, the summations of perimeter contributions by all fragments in the present statistics were approximately 50% and 60%–80% for cases of We = 655 and 2618, respectively.